Assessing the Evolution of Urban Areas, Vegetation, and Surface Temperature in Dubai Using Remote Sensing - Uppin Prateek; Sabobeb Lara; Mikhai Engy; Ali Tarig (E3S Web of Conferences)
This study uses remote sensing to assess the evolution of Dubai’s urban areas, vegetation, and surface temperature. With Dubai being one of the fastest-growing cities in the world, changes to the urban landscape occur rapidly, making it essential to analyze and plan for sustainable growth. The images were downloaded from the U.S. Geological Survey database, stacked, mosaiced on ERDAS, and clipped using ArcGIS software. The temporal assessment of urban growth and vegetation in Dubai was carried out using five Landsat images, i.e., 2000, 2013, 2016, 2019, and 2022, which provided valuable insights into the city’s environmental and developmental changes through analysis of urban areas’ density, NDVI, and LST from satellite images. The project results show an increase in urban areas over the years, changes in vegetation land, and temperature variations. This aims to improve and plan for future developments with environmental considerations.